2010
DOI: 10.1007/s12274-010-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Gold supported on metal oxides for carbon monoxide oxidation

Abstract: Au has been loaded (1% wt.) on different commercial oxide supports (CuO, La 2 O 3 , Y 2 O 3 , NiO) by three different methods: double impregnation (DIM), liquid-phase reductive deposition (LPRD), and ultrasonication (US). Samples were characterised by N 2 adsorption at -196 °C , high-resolution transmission electron microscopy, selected area electron diffraction, energy dispersive X-ray spectrometry, high-angle annular dark-field imaging (Z-contrast), X-ray diffraction, and temperature programmed reduction. CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 61 publications
(111 reference statements)
5
52
0
Order By: Relevance
“…According to the literature (Potoczna-Petru and Kepinski 2001), the peaks (Table 2) observed in the TPR spectra of Co 3 O 4 are due to the reduction of this species to CoO and the further reduction of the latter to Co. One single peak (Table 2) corresponding to the reduction of CuO to Cu (Solsona et al 2006;Carabineiro et al 2011b) was found for samples doped with this metal.…”
Section: Temperature Programmed Reductionmentioning
confidence: 69%
See 1 more Smart Citation
“…According to the literature (Potoczna-Petru and Kepinski 2001), the peaks (Table 2) observed in the TPR spectra of Co 3 O 4 are due to the reduction of this species to CoO and the further reduction of the latter to Co. One single peak (Table 2) corresponding to the reduction of CuO to Cu (Solsona et al 2006;Carabineiro et al 2011b) was found for samples doped with this metal.…”
Section: Temperature Programmed Reductionmentioning
confidence: 69%
“…The resulting solid was washed repeatedly with distilled water for chloride removal (which is well known to cause sinterization of Au nanoparticles, thus turning them inactive (Bond and Thompson 1999;Bond et al 2006;Thompson 2007, 2010;Carabineiro et al 2010g;Santos et al 2010), and again dried in the oven at *100°C overnight, and used without any further treatment. As far as we know, LPRD has only been used by Sunagawa et al (2008) to prepare Pt and Au catalysts on Fe 2 O 3 , FeOOH, ZrO 2 and TiO 2 supports, and by us for Au/CeO 2 (Carabineiro et al 2010g), Au/CuO (Carabineiro et al 2011b), Au/La 2 O 3 (Carabineiro et al 2011b), Au/MgO (Carabineiro et al 2011a), Au/NiO (Carabineiro et al 2011b), Au/TiO 2 (Santos et al 2010) and Au/Y 2 O 3 (Carabineiro et al 2011b) catalysts. To the best of our knowledge, this is the first report on its use for alumina and doped alumina based supports.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were prepared by several techniques like DIM and LPRD [11], reduction with nitric acid [12] and sol immobilisation method [13]. The latter lead to the best results, as reported in literature for Au-activated carbon (AC) catalysts [14].…”
Section: Physical Chemistrymentioning
confidence: 98%
“…Au was deposited by double impregnation (DIM), liquid-phase reductive deposition (LPRD) and ultrasonication methods [11]. The best results were obtained with Au loaded by DIM on the NiO support.…”
Section: Physical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation